The pharmacology and mechanism of action of Monascus purpureus Went: a scoping review - Liu, Sitong; Xu, Yaxin; Xie, Jinhan; Hu, Jing; Wang, Yuetong; Zhang, Junhua; Lee, Myeong Soo; Hu, Haiyin; Ang, Lin; Ji, Zhaochen (Frontiers in Pharmacology, 2025)
ObjectiveThe aim of this study is to review the recent studies on the pharmacology and mechanism of action of Monascus purpureus Went, analyze its medicinal value, and explore future research directions.MethodA scoping review was conducted by searching the China National Knowledge Infrastructure (CNKI), Wanfang database, VIP database, SinoMed, and PubMed from inception until September 2024. The basic information of the included studies, such as study types, disease types, main components, outcomes, and efficacy, was reviewed and summarized. Methodological quality was assessed using the SYRCLE’s risk of bias assessment tool for animal studies and the Cochrane risk of bias assessment tool for clinical trials.ResultsWe identified 251 studies from the five databases. Among them, 153 were experimental studies, 70 were reviews, and 28 were clinical trials. Of the experimental studies, molecular studies accounted for the largest portion, totaling 80 (52%). Among the reviews, research progress accounted for the most, totaling 41 (59%). The clinical trials studied the effects of Monascus purpureus Went and its related Chinese patent medicines and preparations. Of these, 17 (61%) used Monascus purpureus Went-related Chinese patent medicines and preparations as interventions and 11 (39%) used traditional Chinese medicine (TCM) formulations of Monascus purpureus Went as interventions. In terms of methodological quality, both animal studies and clinical trials related to Monascus purpureus Went showed deficiencies in randomized allocation sequence generation, allocation concealment, and blinding methods.ConclusionWe summarized existing studies on the active ingredients and effects of Monascus purpureus Went and found that it is necessary to improve the generation of random allocation sequences and the application of the blinding method in Monascus purpureus Went-related animal studies and clinical trials. When similar studies are conducted in the future, the specific methods of random assignment should be more clearly described, and blinding methods should be applied to improve the objectivity and accuracy of the studies, thereby providing a reference for selecting future research directions and establishing supporting evidence.